Association of sleep quality, media use and book reading with behavioral problems in early childhood. The Ulm SPATZ Health Study. Issue 1 (24th June 2022) - Ricci, C; Poulain, T; Keil, J; Rothenbacher, D; Genuneit, J
Abstract: Study Objectives: The objective of the study was to investigate the association of sleep quality, media use and book reading on internalizing, externalizing and prosocial behavior in early childhood. Methods: In this cross-sectional study we investigated a data set consisting of three consecutive yearly waves of the prospective Ulm SPATZ Health Study, conducted in southern Germany with 565, 496 and 421 children of 4 to 6 years of age, respectively. Standardized effects of the overall score and subscales of the Children's Sleep Habits Questionnaire, parent-reported child media use and book reading as well as their interaction term on the total score of the Strengths and Difficulties Questionnaire along with its externalizing, internalizing and prosocial subscales were estimated by multivariate adjusted random intercept mixed models. Results: Overall sleep quality was associated more with internalizing than externalizing behavior; parasomnias associated with both behaviors. Night waking and sleep anxiety associated only with internalizing behavior. High levels of media use were associated with less internalizing behavior. More book reading resulted in less externalizing and internalizing behavior but more prosocial behavior. Finally, book reading and media use do not interact to determine child's behavior. Conclusions: The current work supports a strategy of monitoring sleep quality, reducing media use and promoting book reading in order to avoid behavioral problems in early childhood.